The impact of failure to make payment behaviour on the profitability of South African municipal electricity suppliers. - ALIAMUTU, Kansilembo Freddy; MKHIZE, Msizi (PT Keberlanjutan Strategis Indonesia, 2024)
Failure to make payments for labour remains a source of concern in the provision of municipal services in South Africa. According to literature, the tradition of failure to make payment rates from the apartheid period, when widespread civic resistance expressed itself via refusing rate paying. The research investigates the influence of South Africa's failure to make payment behaviour on municipal profitability. The random-effects model is utilised to evaluate the connection among the profitability and failure to make payments for 28 municipalities from 2007 to 2022. The findings show that failure to make payments has negative effects on profitability. Profitability is lowered by R291 with each R1000 higher number of unpaid debts written down. Furthermore, national government funds, the total number of users, and the proportion of home units getting free basic electricity all have a positively impact on profitability. These findings support the necessity for more inventive techniques to transform failure to make payment into a payment behaviour.